Can Global Liquidity Forecast Asset Prices? - Darius, Reginald (IMF Working Papers; Working Paper ;, 2010)
During the period leading up to the global financial crisis many asset classes registered rapid price increases. This coincided with a significant rise in global liquidity. This paper attempts to determine the extent to which the rise in asset prices was influenced by developments in global liquidity. We confirm that global liquidity had a significant impact on the buildup in house prices; however, the impact on equity prices was limited. In contrast to common perception, we find that the impact of global liquidity declined during the period of the Great Moderation. The paper also examines spillovers from global liquidity to domestic variables and concludes that domestic factors generally played a more significant role in house price appreciation relative to global factors. This contradicts the hypothesis of weakened potency of domestic monetary policy in the presence of increased international liquidity.